PENGARUH KINERJA KEUANGAN TERHADAP VOLUME PERDAGANGAN MODAL DENGAN EPS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PERAIH BISNIS INDONESIA AWARD - Tuti Zakiyah (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2018)
The information of capital trading volume would reflect the market reaction toward capital which would be traded by a company. In order to find out the factor affecting share trading volume of a company, investor needs to know the financial work and the achievement reached related with the financial work of the company. The objective of this research is to find out how big the effect of current ratio, return on asset, debt to equity ratio toward trading volume activity is by analizing the value of earning per share as reference before investing. This research is a causal verficative descriptive or cause and effect. The population of the research is the bisnis indonesia award winner year 2013 - 2017. The sampling technique of the research uses purposive sampling method with 35 companies by using cross section technique. Thedata collected are secondary data.The result of the research shows that current ratio, return on asset, debt to equity ratio have unsignificant effect toward earning per share. Partially, the variable of current ratio and return on asset has significant effect toward trading volume activity with significant level of 0.000 and 0.011< 0.005. On the other hand, the variable of debt to equity ratio has unsignificant effect toward trading volume activity. As exogen variable (Y1) or earning per share has unsignificant effect toward trading volume activity, (Y2) is endogen variable. The value of determinant coefficient in the total calculation of exogen variable effect toward trading volume activity is 47,9%.